Impact of Structured Postoperative Surveillance on Survival in Patients with Resected Pancreatic Adenocarcinoma - Jacobsen, Anne; Flessa, Maarten; Abels, Anna-Lena; Czubayko, Franziska; Mittelstädt, Anke; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Cancers, 2025)
Background: This study aimed to investigate whether structured surveillance after resection of PDAC has an impact on survival. Methods: 206 patients who underwent PDAC resection at the University Hospital Erlangen between 2005 and 2020 and survived for at least 90 days postoperatively were included in this retrospective study. The impact of surveillance (structured vs. no structured surveillance) respectively of recurrence patterns (recurrence in follow-up vs. symptomatic recurrence) on overall and disease-free survival was investigated. Results: A total of 157 patients (76%) participated in a structured surveillance program after pancreatic resection. During a mean follow-up of 28.5 months, 137 patients (67%) developed recurrence. Patients with structured surveillance showed significantly better outcomes for overall survival after surgery (OSaS: 29.2 months with structured surveillance vs. 16.4 months without, p < 0.001), overall survival after recurrence (OSaR: 10.8 months vs. 3.6 months, p < 0.001), and disease-free survival (DFS: 14.8 months vs. 11.4 months, p = 0.010). In a subgroup analysis of 112 patients with recurrence, survival benefits were observed for those whose recurrence was detected during follow-up compared to those with symptomatic recurrence (OSaS: 24.8 months in the follow-up group vs. 17.2 months in the symptomatic group, p < 0.001; OSaR: 12.6 months vs. 6.5 months, p < 0.001). Conclusion: This study provides evidence that structured surveillance after PDAC resection is beneficial for both overall and disease-free survival. However, randomized studies are needed to confirm the positive impact of structured surveillance programs on survival after pancreatic resection.
CRIS-Team Scopus Importer:2025-05-23
Keywords: follow-up; pancreatic cancer; pancreatic ductal adenocarcinoma; recurrence; surveillance

Recurrence pattern and its risk factors in patients with resected pancreatic ductal adenocarcinoma – A retrospective analysis of 272 patients - Brunner, Maximilian; Flessa, Maarten; Jacobsen, Anne; Merkel, Susanne; Krautz, Christian; Weber, Georg; Grützmann, Robert (Pancreatology, 2024)
Background: The aim of this study was to investigate the patterns of recurrence and their associated risk factors in patients who underwent resection for pancreatic carcinoma. Methods: This retrospective study included 272 patients, who underwent Ro/R1-resection of PDAC from 2005 to 2020 at the University Hospital Erlangen. Risk factors for different recurrence patterns and the prognostic value of recurrence pattern on the overall survival after recurrence were evaluated. Results: 61 % of the patients experienced recurrence, mostly within the first 12 postoperative months (62 %) and in the form of metastases (87 %). The median overall survival from recurrence was 9.2 months. The preoperative absence of diabetes and the presence of lymph node metastasis were independent risk factors for recurrence and a preoperative CA19-9 exceeding 97 U/ml for early recurrence. Additionally, lymph node metastases were associated with a higher risk of metastatic recurrence. Early recurrence, but not the site of recurrence, was identified as an independent prognostic factor for worse overall survival from recurrence. Conclusion: The occurrence of recurrence and especially of early and metastatic recurrence are associated with a worse overall survival. Patients lacking preoperative diabetes, having high preoperative CA19-9 values and lymph node metastases are particularly at risk for (early) recurrence.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Early recurrence; Locoregional recurrence; Overall survival; Pancreatic ductal adenocarcinoma; Recurrence; Resection; Surgery